2012
DOI: 10.1103/physrevb.85.205104
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-tuned insulator to metal transition inEu2Ir2O7

Abstract: We have studied the effect of pressure on the pyrochlore iridate Eu 2 Ir 2 O 7 , which, at ambient pressure, has a thermally driven insulator to metal transition at T MI ∼ 120 K. As a function of pressure, the insulating gap closes, apparently continuously near P ∼ 6 GPa. However, rather than T MI going to zero as expected, the insulating ground state crosses over to a metallic state with a negative temperature coefficient of resistivity, suggesting that these ground states have a novel character. The high-tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
93
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 28 publications
19
93
3
Order By: Relevance
“…In addition, we observe no pressureinduced structural transitions or symmetry changes for applied pressures up to 17 GPa. This result has direct implications for recent high pressure transport studies by Tafti et al 28 , which reported pressure-induced metalinsulator (low temperature) or metal-incoherent metal (high temperature) transitions in Eu 2 Ir 2 O 7 around 6-8 GPa. Since our experimental results have demonstrated that no structural anomalies occur in the vicinity of the critical pressure, we can conclude that these pressureinduced transitions are likely driven by purely electronic effects.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, we observe no pressureinduced structural transitions or symmetry changes for applied pressures up to 17 GPa. This result has direct implications for recent high pressure transport studies by Tafti et al 28 , which reported pressure-induced metalinsulator (low temperature) or metal-incoherent metal (high temperature) transitions in Eu 2 Ir 2 O 7 around 6-8 GPa. Since our experimental results have demonstrated that no structural anomalies occur in the vicinity of the critical pressure, we can conclude that these pressureinduced transitions are likely driven by purely electronic effects.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, MITs and antiferromagnetic ordering in 5d pyrochlores, A 2 B 2 O 7 (B ¼ Ir, Os), have received much attention due to their strong correlation and the key role they play in novel phases. The MITs in these compounds [3][4][5][6][7][8] reportedly are prompted by the emergence of magnetic ordering. Such magnetism-driven MITs are expected to induce exotic phenomena, including a Weyl semimetal [9][10][11][12] and quantum criticality [13] in rare-earth pyrochlore iridates.…”
mentioning
confidence: 99%
“…In particular, rare-earth pyrochlore iridates R 2 Ir 2 O 7 (R = rare-earth elements) provide an ideal class of materials because they have been reported to show a variety of transport and magnetic behaviors [5][6][7][8] , varying from a correlated metal [9][10][11] to an insulator 12,13 depending on the ionic radius of rare-earth elements. They are also attractive because the one hole nature of Ir 4+ 5d t 5 2g state simplifies the electronic structure and allows further in depth comparison between experiment and theory.…”
mentioning
confidence: 99%
“…13 According to the theoretical prediction, it is likely that the diffusive metallic phase under pressure may well correspond to the topological semi-metallic phase. Further study on the properties of this state under pressure is highly desired to elucidate the exotic nature of the ground state.…”
mentioning
confidence: 99%